A non-orthogonal material model of woven composites in the preforming process. Issue 1 (2017) - Zhang, Weizhao; Ren, Huaqing; Liang, Biao; Zeng, Danielle; Su, Xuming; Dahl, Jeffrey; Mirdamadi, Mansour; Zhao, Qiangsheng; Cao, Jian
Abstract: Woven composites are considered as a promising material choice for lightweight applications. An improved non-orthogonal material model that can decouple the strong tension and weak shear behavior of the woven composite under large shear deformation is proposed for simulating the preforming of woven composites. The tension, shear and compression moduli in the model are calibrated using the tension, bias-extension and bending experiments, respectively. The interaction between the composite layers is characterized by a sliding test. The newly developed material model is implemented in the commercial finite element software LS-DYNA ® and validated by a double dome study.